Electroactive biofilms: Current status and future research needs - Borole, Abhijeet P.; Reguera, Gemma; Ringeisen, Bradley; Wang, Zhi-Wu; Feng, Yujie; Kim, Byung Hong (Royal Society of Chemistry, 2011)
Electroactive biofilms (EABFs) generated by electrochemically active microorganisms have many potential applications in bioenergy and chemicals production. Biofilm electroactivity can have a significant impact on the yield and efficiency of the conversion processes. This review assesses the effects of process and design parameters on the growth and activity of biofilms in bioelectrochemical systems (BESs). First we compare the role of planktonic and biofilm-forming microorganisms in BESs. The effect of physical, chemical, and electrochemical operating parameters such as flow rate, temperature, pH, ionic strength, substrate concentration and loading, external resistance, and redox potential on EABF attributes such as growth rate, exoelectrogen population, formation of extracellular polymeric substances, mediator synthesis, and rate of electron transfer are discussed. The relationship between electrochemical performance and operating parameters is also examined to identify gaps in assessment and the potential role of future modeling efforts. Similarly, we review what is currently known about the mechanisms that enable electroactive biofilms to transfer electrons and also the contribution of the electrical conductivity of the biofilms' exopolymeric components to BES performance. The current status of cathodic biofilms is also reviewed. Complementary approaches that use process control to optimize EABF composition and biomass density, while minimizing mass transfer effects and changes to system design parameters, are likely necessary to improve BES performance to a level needed for commercial consideration. Finally, future research needs that enable better understanding and optimization of the performance of EABFs are outlined.
Keywords: MICROBIAL FUEL-CELLS; EXTRACELLULAR POLYMERIC SUBSTANCES; WASTE-WATER TREATMENT; GEOBACTER-SULFURREDUCENS BIOFILMS; CONTINUOUS ELECTRICITY-GENERATION; CATHODIC OXYGEN REDUCTION; METAL-REDUCING BACTERIUM; MIXED CULTURE BIOFILMS; SHEWANELLA-ONEIDENSIS; POWER-GENERATION